The demographic bonus and shifting health insurance risk profiles among the productive age population in Indonesia: A literature review - Assyifa Ramadhani; Reynanda Sabrina; Robby Firmansyah; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
Background: Indonesia is currently experiencing a demographic bonus, with the productive age population accounting for 69.3% of the total population. While this presents an economic opportunity, it poses significant challenges to the health sector due to an epidemiological transition toward Non Communicable Diseases (NCDs), which contribute to 74% of global mortality. Objective: This study aims to analyze the impact of the demographic bonus on the shifting health risk profiles of the productive age group and its implications for claim trends and the sustainability of the health insurance system in Indonesia. Methods: A systematic literature review was conducted using the Google Scholar database. The search strategy employed keywords related to demographics, NCDs, and health financing, with a publication filter for the last ten years (2016–2026). Data were analyzed using a descriptive narrative approach to synthesize relevant findings. Results: The findings indicate that the dominance of the productive age population, coupled with unhealthy lifestyle behaviors, has triggered a rise in chronic disease prevalence requiring long term medical management. This shift directly correlates with a surge in healthcare service utilization and claim burdens within the National Health Insurance (JKN) scheme. However, current insurance benefit designs remain heavily focused on curative services (85.4%), while promotive preventive efforts at primary care facilities remain suboptimal. The imbalance between increased utilization and financing capacity potentially threatens risk pool stability and risks financial deficits. Conclusion: The demographic bonus may become an economic burden without an adaptive health system transformation. Strengthening promotive preventive policies and innovative chronic disease management are essential to control medical costs. Cross sector synergy is crucial to ensure a healthy productive age population and the long term sustainability of the JKN program.